Exploring the Role of Virtual Reality to Support Clinical Diabetes Training—A Pilot Study. (July 2022) - Mallik, Ritwika; Patel, Mayank; Atkinson, Ben; Kar, Partha
Background: It is estimated that 16 to 25% of patients in hospital have diabetes and 1 in 25 inpatients with Type 1 Diabetes develop diabetic ketoacidosis (DKA). It is vital that non-specialist doctors recognize and appropriately manage diabetes emergencies. Simulation training is increasingly being used in healthcare and virtual reality (VR) based educational resources is transforming medical education. This study aimed to evaluate the use of virtual reality to help non-specialist clinicians manage clinical scenarios related to diabetes. Methods: This pilot project, titled 'DEVICE' (Diabetes Emergencies: Virtual Interactive Clinical Education) was developed in collaboration with Oxford Medical Simulation. Fully interactive immersive VR scenarios were created to stimulate real life diabetes emergencies. Users then received personalized feedback and performance metrics. Feedback surveys were provided before and after the participation in the VR scenario. Kirkpatrick's training evaluation model was used. Results: Thirty-nine participants from 2 hospitals in UK provided feedback up to 3 months after attending the VR education sessions. Overall feedback was extremely positive, and participants found this immersive teaching experience very helpful. After use of virtual reality scenarios, the mean trainee confidence in managing DKA (on an 8-point Likert scale) increased from 3.92 (3.38-4.47) 95% CI to 5.41 (4.79-6.03) 95% CI (statistically significant). The VR study demonstrates Kirkpatrick level 3 in the follow up survey. Conclusion: VR based training scenarios in this pilot project increased confidence in managing diabetes emergencies and demonstrated positive changes in their behavior. VR education is a safe, useful and a well-liked training tool for diabetes emergencies.